Power Management for Stationary Machines - CAHILL, VINNY (My University, 2005)
This paper examines effective power management of users? stationary desktop PCs in a pervasive computing office environment. The objective being to minimise the building?s electricity consumption while maintaining acceptable desktop PC performance. Current state of the art power management is focused on developing polices for mobile devices, which are ineffective for stationary machines. Effective stationary policies need to obtain context from the user of the machine, but there is a balance between what detail of context is necessary and how much this extra context costs both monetarily and energy wise. We have implemented two location aware policies which detect presence of the user?s Bluetooth enabled mobile phone. Trial results indicate that with these policies it is possible to get within 8% of optimal energy consumption with little performance degrade. However, this is the best case and the results are dependent on the user?s usage patterns and the geographical layout of the office.
Proceedings of the 38th Hawaii International Conference on System Sciences
38th Hawaii International Conference on System Sciences - 2005
PUBLISHED
Hawaii
ISBN ~ ISSN:1530-1605 , 0-7695-2268-8-9
Keywords: Computer Science